Fundamentals of Internet of things : for students and professionals / Farzin John Dian. - Dian, F. John (Wiley-IEEE Press, 2023)
'Fundamentals of Internet of Things' teaches the principles of IoT systems. It employs a systematic approach to explain IoT architecture models and their layers. The textbook is arranged based on various layers of an architecture model. For readers who are unfamiliar with the concept of data communication and networks, the first chapter of this book covers the fundamentals of data communication and networks. It can also be used as review material for those who are already familiar with the concept.